Suppressive Effects of Glycyrrhetinic Acid Derivatives on Tachykinin Receptor Activation and Hyperalgesia - Yuko Akasaka; Atsushi Sakai; Kumiko Takasu; Michiko Tsukahara; Akira Hatta; Hidenori Suzuki; Hideo Inoue (Elsevier, 2011)
Abstract.: Glycyrrhetinic acid (GA), an aglycone of glycyrrhizin, isolated from the licorice root (Glycyrrhizia), and its semi-synthetic derivatives have a wide range of pharmacological effects. To investigate whether GA derivatives may be used as a new class of analgesics, we examined the effects of these compounds on human tachykinin receptors expressed in CHO-K1 cells. Among the GA derivatives examined, the disodium salt of olean-11,13(18)-dien-3β,30-O-dihemiphthalate inhibited the mobilization of [Ca2+]i induced by substance P, neurokinin A, and neurokinin B in CHO-K1 cells expressing the human NK1, NK2, and NK3 tachykinin receptors, respectively. In an inflammatory pain model, Compound 5 suppressed the capsaicin-induced flinching behavior in a dose-dependent manner. Compound 5 was also effective in suppressing pain-related behaviors in the late phase of the formalin test and reducing thermal hyperalgesia in the neuropathic pain state caused by sciatic nerve injury. Collectively, Compound 5 may be an analgesic candidate via tachykinin receptor antagonism. Keywords:: glycyrrhetinic acid, inflammatory pain, neuropathic pain, substance P, tachykinin receptor